Regulatory power of pre-autonomous entities - Matas Morro, Vicente (Revista de Estudios de la Administración Local y Autonómica, 1983)
SUMMARY: I. DEFINITION. - II. CLASSES OF REGULATIONS. - III. EXERCISE OF THE REGULATORY POWER OF THE PRE-AUTONOMIC BODIES: 1. REGULATION OF INTERNAL REGIME. 2. REGULATION OF TRANSFERRED MATERIALS. - IV. REQUIREMENTS FOR ITS EXERCISE: 1. BASIC. 2. IN WAY: A) REGULATION OF INTERNAL REGIME. B) TRANSFERRED COMPETENCES.